2011
DOI: 10.1038/nmat3179
|View full text |Cite
|
Sign up to set email alerts
|

Collective osmotic shock in ordered materials

Abstract: Osmotic shock in a vesicle or cell is the stress build-up and subsequent rupture of the phospholipid membrane that occurs when a relatively high concentration of salt is unable to cross the membrane and instead an inflow of water alleviates the salt concentration gradient. This is a well-known failure mechanism for cells and vesicles (for example, hypotonic shock) and metal alloys (for example, hydrogen embrittlement). We propose the concept of collective osmotic shock, whereby a coordinated explosive fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…Furthermore, membranes based on such microporous materials have not found commercial applications in gas separation because of scale-up impracticalities and high cost 9 . Polymer membranes provide an energy-efficient method of gas separation because they do not require thermal regeneration, a phase change or active moving parts in their operation; therefore, they are expected to play a growing role in an energy-constrained and low-carbon future [10][11][12][13][14][15] . Most commercial polymer membranes for gas separation have been limited to a small number of polymers with low permeability and high selectivity, creating the need for large areas to compensate for the lack of permeance.…”
mentioning
confidence: 99%
“…Furthermore, membranes based on such microporous materials have not found commercial applications in gas separation because of scale-up impracticalities and high cost 9 . Polymer membranes provide an energy-efficient method of gas separation because they do not require thermal regeneration, a phase change or active moving parts in their operation; therefore, they are expected to play a growing role in an energy-constrained and low-carbon future [10][11][12][13][14][15] . Most commercial polymer membranes for gas separation have been limited to a small number of polymers with low permeability and high selectivity, creating the need for large areas to compensate for the lack of permeance.…”
mentioning
confidence: 99%
“…State-of-the-art polymeric gas-separation membranes are subject to a trade-off between permeability and selectivity, as theoretically predicted by Freeman 2 , also known as the Robeson's upper bound [3][4] . Research of the next-generation separation membrane is focused on tuning both local chemical interactions and pore sizes towards the kinetic diameter of molecules to achieve both selective separation and high throughput 1,[5][6][7][8][9][10][11][12][13][14] . Over the past decade, significant progress has been made in molecular sieving materials such as carbon-based membranes (for example, carbon nanotubes [15][16] and graphene 9 ) and zeolites 7 .…”
mentioning
confidence: 99%
“…Ultraviolet light irradiation is a widely used technique for processing of polymer materials 8,[37][38][39][40] , for example, polymerization of novel gas-separation membranes 40 , creating nanostructures from block copolymer 8 , or surface modification of polymeric films (for example, polyimides and polydimethylsiloxane) 8,[37][38][39] . Enhancement of membrane-separation properties by ultraviolet surface modification is not uncommon.…”
mentioning
confidence: 99%
“…[ 20,21 ] Very recently, some of us proved that a porous stratifi ed structure displaying strong refl ection peaks in the UV range can be attained from a block copolymer (BCP) fi lm. [ 22 ] In particular, it was demonstrated that a fi lm made of a diblock copolymer containing polystyrene (PS) and polymethyl methacrylate (PMMA), in brief [poly(styreneblock -methyl methacrylate) PS-b -PMMA)], can be used as starting material to attain ordered porous multilayers through a process that involves collective osmotic shock (COS). The fi nal structure shows alternate dense and porous layers, with signifi cant refractive index contrast, which endow it with photonic crystal properties in the UV range.…”
mentioning
confidence: 99%